Sex‐specific associations of Roseburia with uric acid metabolism and hyperuricemia risk in females - Zhihan Yang; Zeng Zhang; Mohan Chen; Jin Hu; Yingqi Qiu; Shijia Lin; Xiaolu Zhou; Jiachao Zhang; Shuaiming Jiang (iMetaOmics)
Abstract Hyperuricemia (HUA) affects approximately 14% of the population, with a marked gender disparity showing lower incidence in females. While the role of gut microbiota in HUA has been extensively studied in males, its influence in females remains unclear. This study recruited 623 participants, including 270 females, to explore this gap using 16S rDNA sequencing. We found that Roseburia was significantly enriched in healthy females and negatively correlated with estrogen (E2) and uric acid (UA) levels. Validation using three published cohorts (256 samples) confirmed Roseburia as a critical genus for UA regulation. Mechanistically, Roseburia was positively correlated with the xanthine‐glycine metabolic pathway, which may influence UA production in females. These findings shed light on gender differences in HUA incidence from a gut microbiota perspective and propose Roseburia as a promising target for probiotic‐based prevention of HUA in females.